Amino Acid Catabolism During Nitrogen Limitation in Phaeodactylum tricornutum - Pan, Yufang; Hu, Fan; Yu, Chen; Li, Chenjie; Huang, Teng; Hu, Hanhua (Frontiers in Plant Science, 2020)
Diatoms can accumulate high levels of triacylglycerols (TAGs) under nitrogen depletion and have attracted increasing attention as a potential system for biofuel production. In Phaeodactylum tricornutum, a model diatom, about 40% of lipid is synthesized from the breakdown of cellular components under nitrogen starvation. Our previous studies indicated that carbon skeletons from enhanced branched-chain amino acid (BCAA) degradation under nitrogen deficiency contribute to TAG biosynthesis in P. tricornutum. In this review, we outlined the catabolic pathways of all 20 amino acids based on the genome, transcriptome, proteome and metabolome data. The contribution of these amino acid catabolic pathways to TAG accumulation was also analyzed.